THE PROFILE AND MARKETING STRATEGY OF PHIA DEVA COMPANY AS THE SPECIAL GIFT FROM YOGYAKARTA - , WEDHA SEKAR PUSPITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper aims to explain about the profile of Phia Deva Company and the marketing strategies used by Phia Deva Company. Furthermore, this graduating paper describes about some marketing strategies which use of Phia Deva Company, such as